(untitled) (Itinera, 2022)
In this essay I aim to draw close to an exceptional case study in American modernist art theory: Clement Greenberg’s reinterpretation of Flemish and Dutch painting. I will focus on it in connection with the Greenbergian vision of modernism as a whole. Firstly, I will make a genealogy of the “Flemish turn” in the history of aesthetics, by analyzing the key moments (Winckelmann, Hegel, Baudelaire) in which the so-called Northern Primitives have served to frame modern painting, in contrast to Southern classic Renaissance. Then, I will concentrate on Greenberg’s use of this heritage, by comparing his linking Flemish colour with photography to Svetlana Alpers’ notion of “art of describing”. It will emerge that an original interaction between colour and photography is given, that is suitable both to the notion of realism and to its modernist acceptance.